2022
DOI: 10.7759/cureus.30432
|View full text |Cite
|
Sign up to set email alerts
|

Does Vitamin D Have a Role in Diabetes?

Abstract: Vitamin D, a fat-soluble vitamin, acts in the calcium and phosphorus metabolism in its active form (1,25dihydroxy vitamin D). It may help prevent and treat autoimmune diseases, including diabetes mellitus. Diabetes has become a significant global health issue with a rising incidence and prevalence. A recent focus has been on vitamin D supplementation as part of efforts to discover novel ways to prevent and treat diabetes. Most evidence points to the vitamin D receptors (VDRS) gene in both types of diabetes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
1
3
0
2
Order By: Relevance
“…Previous studies have shown that su cient vitamin D levels protect against diabetes, and vitamin D de ciency is associated with diabetes progression and a higher prevalence of diabetic nephropathy [24,25]. Therefore, consistent with our study's result, people with lower vitamin D levels have a higher risk of progression in their nephropathy and more elevated UACR.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that su cient vitamin D levels protect against diabetes, and vitamin D de ciency is associated with diabetes progression and a higher prevalence of diabetic nephropathy [24,25]. Therefore, consistent with our study's result, people with lower vitamin D levels have a higher risk of progression in their nephropathy and more elevated UACR.…”
Section: Discussionsupporting
confidence: 92%
“…A countless number of studies unveiling the antidiabetic properties, including early preventive, disease course modifying, and complication limiting effects, of individual nutrients and phytochemicals that are ubiquitously present in BP from different botanical and geographical origins have been published so far. This includes, for example, nutrients including vitamins such as groups B [ 241 , 242 , 243 ], C [ 244 , 245 , 246 ], D [ 247 , 248 , 249 ], and E [ 128 , 250 , 251 ], oligo-elements and other minerals [ 252 , 253 , 254 ], and lipids such as unsaturated fatty acids [ 255 , 256 , 257 ] and phytosterols [ 63 , 258 , 259 ], as well as other phytochemicals including polyphenols such as phenolic acids, flavonoids, and stilbenes (very recent and comprehensive reviews of preclinical and clinical evidence can be found in [ 260 , 261 , 262 , 263 , 264 , 265 , 266 ]). Despite the substantial amount of experimental and clinical evidence of all these BP compounds in the complex pathophysiology of diabetes and in its interaction with other comorbidities, the possible synergistic potential and real clinical outcome of these compounds, which are always combined in BP, have generally been omitted in research and must be further studied by in vivo experiments, and subsequently verified and objectively assessed by clinical studies.…”
Section: Resultsmentioning
confidence: 99%
“…(6) Our research focuses exclusively on bone. Other pathologies, such as breast and colon cancer [ 47 ], autoimmune diseases [ 48 ], or diabetes [ 49 ], might benefit from earlier supplementation. Therefore, our results should not be interpreted as not to supplement subjects with a value of 20 ng/ml, which may be adequate for bone and muscle health, but not for the rest of the body.…”
Section: Discussionmentioning
confidence: 99%